Drifter Observations Reveal Intense Vertical Velocity in a Surface Ocean Front. Issue 18 (22nd September 2022) - Tarry, Daniel R.; Ruiz, Simón; Johnston, T. M. Shaun; Poulain, Pierre‐Marie; Özgökmen, Tamay; Centurioni, Luca R.; Berta, Maristella; Esposito, Giovanni; Farrar, J. Thomas; Mahadevan, Amala; Pascual, Ananda
Abstract: Measuring vertical motions represent a challenge as they are typically 3–4 orders of magnitude smaller than the horizontal velocities. Here, we show that surface vertical velocities are intensified at submesoscales and are dominated by high frequency variability. We use drifter observations to calculate divergence and vertical velocities in the upper 15 m of the water column at two different horizontal scales. The drifters, deployed at the edge of a mesoscale eddy in the Alboran Sea, show an area of strong convergence ( O $\mathcal{O}$ ( f )) associated with vertical velocities of −100 m day −1 . This study shows that a multilayered‐drifter array can be an effective tool for estimating vertical velocity near the ocean surface. Plain Language Summary: The study of vertical motions in the ocean is a key challenge as they are difficult to measure and predict although their impact is crucial on the exchange of water properties in the water column. Here, we use high resolution drifter observations to calculate vertical velocities in the upper layers of a surface density front. This study shows high values of downward speed combined with a high temporal variability at the surface layer. Key Points: Horizontal divergence and vertical vorticity computed from drifter observations Maximum downward speeds of 100 m day −1 in the upper 15 m on a subducting region The vertical velocity time series shows a high temporal variability, varying from 50 to −100 m day −1 over 4 hr